Impact of a psychomotor massage program on the quality of life of institucionalized elderly people. - Roque, Gisela (2018)
INTRODUCTION The world’s population is ageing (United Nations, 2015). Therefore the number of older people who are dependent on others, who have reduced mobility and physical and/or mental2009). So, our objective was to analyze the effect of a therapeutic intervention based on psychomotor massage on quality of life indicators of institutionalized elderly people. METHODS The present study included 13 participants aged 63-94 years, without severe cognitive impairment, residing in a nursing home. First, participants (control group) maintained their daily life activities for 4 weeks. Second, participants (experimental group) attended the intervention, two days a week for a period of 8 weeks. The therapeutic intervention program was based on 30-minute sessions of psychomotor massage. Four weeks after the intervention, there was a follow-up. Physical mobility, pain, energy, emotional reactions, sleep and social isolation were assessed through the Nottingham Health Profile questionnaire. RESULTS: Participants improvements in pain (p<.001), physical mobility (p=.049), energy (p =.012), emotional health problems, has been progressively increasing. These scenarios often lead to institutionalization, which has been associated with the loss of quality of life (Luppa, et al.,reactions (p=.002), sleep (p=.017), social isolation (p=.013), and health status (p=.001). CONCLUSIONS This study represents a first approach to the application of a psychomotor massage technique as a therapeutic intervention in nursing homes for the elderly. The method appears to be effective in enhancing health and quality of life of institutionalized elderly persons. This psychomotor technique could be considered as an option for achieving health benefits with a low cost for nursing homes, but further studies using this technique in larger samples are needed to confirm the trends observed in the present study.